ANALISIS KEUNTUNGAN USAHA INDUSTRI TAHU â€œPURWANTOâ€ DI KELURAHAN MALALAYANG SATU TIMUR KECAMATAN MALALAYANG - Mitias ., Yoman; Juliana Ruth Mandei; Grace Adonia Josefina Rumagit (Sam Ratulangi University, 2021)
This study aims to determine the business benefits of Purwanto Tofu Industry in the East Malalayang Satu Village, Malalayang District. This research was carried out during October to December 2020 starting from preparation to compiling a report on the research site in the Malalayang Satu Timur Village, Malalayang District. The data used in this study are primary data and secondary data. Primary data was obtained through direct interviews with tofu industry owners using a list of questions/(questionnaires). While the secondary data was taken from the malalayang village office, east of the malalayang sub-district. The results of this study indicate that Purwanto's tofu industry is a small-scale business that uses soybeans as raw materials to be processed into tofu. The business owner's production process activities are assisted by 4 workers from within the family. Purwanto's tofu industry is an individual business or a household business. The source of capital used in producing tofu is its own capital for the continuity of its business. Purwanto's Tofu Industry Business shows that it has a profit, amounting to IDR. 45,492,500.00 per month.